Addiction & recovery - Shepley, Nick (Andrews UK, 2011)
All the best recovery meetings I have ever been to start with a story, so I will tell you mine. If you identify with it - good - but try to look for the similarities and not the differences. Addiction and Recovery is contains teachings from many different sources; some are the ideas of eminent psychologists, others are from the pages of spiritual books and the minds of spiritual thinkers. Much of the book combines aspects of the AA 12 Step Programme. However, this book is not endorsed by the ...